Health Implications of Housing Assignments for Incarcerated Transgender Women - Ledesma, Elida (Am J Public Health, 2020)
Transgender women (i.e., persons who were assigned male sex at birth but who live and identify as female) experience forms of discrimination that limit their access to stable housing and contribute to high rates of incarceration; once incarcerated, the approaches used to assign them housing within the jail or prison place them at risk for abuse, rape, and other outcomes. Yet, a paucity of studies explores the implications of carceral housing assignments for transgender women. Whether the approaches used to assign housing in jails and prisons violate the rights of incarcerated transgender persons has been argued before the US federal courts under Section 1983 of the US Constitution, which allows persons who were raped while incarcerated to claim a violation of their Eighth Amendment rights. Reforms and policy recommendations have been attempted; however, the results have been mixed and the public health implications have received limited attention.